Hubungan Kelengkapan Alat Pelindung Diri, Lama Pembagian Waktu Kerja, dan Pemahaman Pekerja Tentang Briefing dengan Kecelakaan Kerja di Pabrik Kelapa Sawit PT. Bukit Barisan Indah Prima Jambi - Armaidi Darmawan; Irawati Sukandar; Oktavia Sulistiana (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2014)
ABSTRACT Background: Occupational accident is an accident related to work implementation caused by work implementation factor or an accident occurring at workplace or an unpredictable and unexpected incident that mess up the process of work activities. Several factors related to occupational work among others are self-protection tools, distribution length of working time in one day and workers’ understanding regarding briefing by a company. Methods : This study is a correlative analysis applying cross sectional design. The population of this study are registered employees of palm oil factory of PT Bukit Barisan Indah Prima. The number of samples conducted for this study is 107. The data taken regarding the completeness of self-protection tools, length distribution of working time in one day, the workers’ understanding regarding briefing and occupational accidents by conducting a direct interview following questionnaire at palm oil factory of PT Bukit Barisan Indah Prima. Result: The study showed that variable of the occurrence of occupational accident having an accident was 35 (32.7%, 18.7% of workers not having a complete self-protection tool had ever experienced an occupational accident. Of 18.7% workers who has working hours more than 7 hours had ever experienced an accident, and 14% of workers having enough working hours (7 hours) had an accident. Of 22.4% workers who do not understand briefing had ever had an accident, and 10.3% of workers who understand briefing had an accident. Conclusion All risk factors (self-protection tool, length distribution of working hours in one day, and workers’ understanding regarding briefing) are related to occupational accidents. Keywords: occupational accident, self-protection tool, length distribution of working hours in one day, workers’ understanding regarding briefing.